Impaired β-cell function attenuates training effects by reducing the increase in heart rate reserve in patients with myocardial infarction. Issue 2 (February 2015) - Omiya, Kazuto; Minami, Keisuke; Sato, Yukio; Takai, Manabu; Takahashi, Eiji; Hayashi, Akio; Yamauchi, Masahiro; Suzuki, Kengo; Akashi, Yoshihiro J.; Osada, Naohiko; Izawa, Kazuhiro P.; Watanabe, Satoshi
Abstract: Background: Insulin resistance (IR) is characterized as a metabolic disorder syndrome that is upstream of hypertension, dyslipidemia, and diabetes mellitus (DM). This study investigated exercise training effects on the exercise tolerance and heart rate dynamics in patients with IR or pancreatic β-cell dysfunction. Methods: Seventy patients (mean age, 60.1 years) with myocardial infarction (MI) participating in a phase II cardiac rehabilitation program were studied. Patients diagnosed with DM were excluded. Homeostasis model-assessment indices were used to divide patients into three groups – A: IR; B: normal; and C: β-cell dysfunction. A cardiopulmonary exercise test (CPX) was performed and peak oxygen uptake ( V ˙ O 2 ) was measured. After baseline testing, subjects participated in a supervised, combined aerobic and resistance exercise program. Results: Peak V ˙ O 2 at baseline was comparable among the three groups, and it improved after training in all groups ( p  < 0.05). However, both the increase and percentage increase in peak V ˙ O 2 were smaller in Group C than in Group A ( p  < 0.05). Heart rate (HR) reserve (peak HR−rest HR), and HR recovery immediately 1 min after exercise during CPX were calculated in 45 patients who were not taking negative chronotropic agents. Group C alone did not show any significant increase in HR reserve. HR reserve at both baseline and after training had significant positive correlations with peak V ˙ O 2 . HR recovery was 1.9 beats/min lower in group C than group A, but this was not significant. HR recovery in group C did not increase after cardiac rehabilitation. Conclusion: Impaired HR reserve increase after training in patients with pancreatic β-cell dysfunction attenuates exercise training effects on functional capacity. Comprehensive treatment including vigorous exercise training will be needed in such prediabetic patients.